THE EFFORTS TO IMPROVE STUDENT’S BLOCKING LEARNING OUTCOMES IN VOLLEYBALL GAMES BY APPLICATION OF LEARNING VARIATION - Ardhi Surya Wijaya; Indra Kasih; Budi Valianto (Indonesia Sport Journal, 2021)
The research is purposed to recognize improvement student’s blocking learning outcomes in volleyball games by application of learning variation. Subject of research is the whole of XI IPS 1 students of Dolok Batu Nanggar Public High School 1. The method that used in research is Classroom Action Research. The results of the research are : (1) learning outcomes on cycle 1 get 19 students as 50% has reached the level of completeness and the average score is 68; (2) learning outcomes on cycle 2 get 33 students as 86,84% has reached the level of completeness and the average score is 86,24%. The improvement of learning outcomes is 12,85%; (3) Based on analysis that application of learning variation get improve in blocking learning process on XI IPS 1 students of Dolok Batu Nanggar Public High School 1.Keywords : Classroom Action Research, learning outcomes